Theological neuroethics : Christian ethics meets the science of the human brain - Messer, Neil (T & T Clark Enquiries in Theological Ethics Ser., 2017)
"Neil Messer brings together a range of theoretical and practical questions raised by current research on the human brain: questions about both the 'ethics of neuroscience' and the 'neuroscience of ethics'. While some of these are familiar to theologians, others have been more or less ignored hitherto, and the field of neuroethics as a whole has received little theological attention. Drawing on both theological ethics and the science-and-theology field, Messer discusses cognitive-scientific and neuroscientific studies of religion, arguing that they do not give grounds to dismiss theological perspectives on the human self. He examines a representative range of topics across the whole field of neuroethics, including consciousness, the self and the value of human life; the neuroscience of morality; determinism, freewill and moral responsibility; and the ethics of cognitive enhancement."--Bloomsbury Publishing